Practical theology confronting the crisis in nature and climate (Nordic Journal of Practical Theology, 2024)
Nature and climate issues are not in the news. News media offer constant reports about storms, floods and disturbing research findings. When it comes to people's practical and political engagement, it still seems to be the immediate things that matter. We do not need to go to the recent American election to make such observations. In October 2024, the analysis agency Kantar presented its annual climate barometer, which shows that climate engagement among the Norwegian population is falling in all age groups. While climate engagement was a top issue a few years ago, it now ranks fifth in the list of challenges Norwegians believe the country is facing. The economy, crime and health issues are more worrying. The analysis agency wonders if there is a resignation spreading. What consequences should the situation have for theological work?